2022
DOI: 10.3390/ijms232314718
|View full text |Cite
|
Sign up to set email alerts
|

Oleic Acid Facilitates Cd Excretion by Increasing the Abundance of Burkholderia in Cd-Exposed Mice

Abstract: As a global pollutant, cadmium (Cd) can easily enter the body through food chains, threatening human health. Most Cd is initially absorbed in the gut, with the gut microbiota playing a pivotal role in reducing Cd absorption and accumulation. This study assessed the effects of three fatty acids on Cd accumulation and toxicity in Cd-exposed mice. The results showed that oleic acid (OA) was the most effective in facilitating Cd excretion in mice among these fatty acids. The use of OA led to reduced Cd accumulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 71 publications
1
7
0
Order By: Relevance
“…In addition, oral administration of Akkermansia muciniphila was found to reduce Cd accumulation in the kidneys and livers of mice [57]. Burkholderia is able to promote Cd excretion by secreting extracellular polymeric substances [27]. Similar in vivo effects were unveiled in the current study when the GM was treated with Thr, leading to significant improvement in the proportion of Escherichia-Shigella, promotion of Cd excretion, and reduction of adverse histopathological changes in guts since fecal excretion is one of the ways for microbiota to detoxify heavy metals [58].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, oral administration of Akkermansia muciniphila was found to reduce Cd accumulation in the kidneys and livers of mice [57]. Burkholderia is able to promote Cd excretion by secreting extracellular polymeric substances [27]. Similar in vivo effects were unveiled in the current study when the GM was treated with Thr, leading to significant improvement in the proportion of Escherichia-Shigella, promotion of Cd excretion, and reduction of adverse histopathological changes in guts since fecal excretion is one of the ways for microbiota to detoxify heavy metals [58].…”
Section: Discussionmentioning
confidence: 99%
“…The abundance of the Clostridium, Lactobacillus, Pseudomonas, and Enterobacterium genus decreased in the guts of Cd-exposed mice [26]. GM also plays a significant role in inhibiting the absorption of Cd in mice [22,27]. Previous studies have described the use of probiotics such as Lactobacillus plantarum HD 48 and CCFM8610 to reduce the level of Cd in the gut [22,25,28].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, fish oil rich in unsaturated fatty acids can regulate gut microbiota [ 13 , 14 ]. Our previous studies have shown that adding the unsaturated fatty acid oleic acid (OA) can reduce Cd accumulation, promote Cd excretion, and significantly restore the diversity of the gut microbiota, confirming the ability of OA to reduce Cd [ 15 ]. Therefore, unsaturated fatty acids can potentially treat Cd poisoning and regulate the gut microbiota.…”
Section: Introductionmentioning
confidence: 95%
“…Studies have shown that Cd exposure disrupts the gut microbiota in mice, leading to increased gut permeability [ 24 ] and a reduced abundance of probiotics such as Lactobacillus and Bifidobacteria [ 25 , 26 ]. Some gut probiotics also play an essential role in promoting Cd excretion [ 15 , 27 ]. For example, in mouse models, Lactobacillus plantarum CCFM8610 can reduce Cd accumulation in organs by increasing Cd levels in feces [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bacillus licheniformis CK1 may degrade ZEN in Lactobacillus broth by producing extracellular chitinase, cellulase, and protease enzymes [131]. Oleic acid promotes Cd excretion by increasing the abundance of Burkholderia [132]. Probiotics and postbiotics can have antioxidant properties and scavenge free radicals.…”
Section: Functional Mechanisms Of Probiotics and Postbioticsmentioning
confidence: 99%